The environmental rule of law for oceans designing legal solutions - Platjouw, Froukje Maria; Pozdnakova, Alla (Cambridge University Press, 2023)
Our oceans need a strong and effective environmental rule of law to protect them against increased pressures and demands, including climate change, pollution, fisheries, shipping and more. The environmental rule of law for oceans requires the existence of a set of rules and policies at multiple governance levels that appropriately regulate human activities at sea and ensure that pressures on the marine ecosystem are tackled effectively. Adhering to the rule of law through clear, predictable, coherent, and legitimate rules, and their implementation and enforcement, is timely and urgent. In this book, we are searching for ways to improve, strengthen and further develop the environmental rule of law for oceans. The book provides future-oriented perspectives on how law should evolve to better preserve the oceans. All chapters incorporate novel insights and ideas for legal solutions that might inspire scholars, actors, authorities, citizens and communities around the globe. This title is Open Access.
Keywords: United Nations Convention on the Law of the Sea -- (1982 December 10)